The Dynamics of Electronic Land Certificate Issuance in the Era of Industrial Revolution 5.0: An Analysis of Security, Legal Policy, and Administrative Protection - Franciscus Xaverius Wartoyo; Meivina Jayanti; Dewi Dewi; Lee Yong Hwa (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
The land sector digital transformation represents a core aspect of Industrial Revolution 5.0 because it requires human-technology collaboration. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) launched electronic land certificates as a strategic move to enhance public administration efficiency and service transparency and land ownership legal certainty. The new system creates multiple difficulties which affect data protection and legal frameworks and administrative safeguarding of land ownership rights. The research investigates electronic land certificate distribution through state administrative law and community legal protection frameworks. The research design combines normative juridical analysis with evaluations of applicable laws and regulations and doctrinal interpretations and judicial decisions and digital technology integration in land administration. The research findings demonstrate that electronic land certificate distribution through blockchain systems or integrated servers provides reliable and efficient operations yet faces security threats and conflicting rules and user digital competence restrictions. The legal framework requires alignment between Law No. 11 of 2008 about Electronic Information and Transactions and Law No. 5 of 1960 about Basic Agrarian Principles and BPN implementing regulations to validate rights holder protection. The Industrial Revolution 5.0 requires electronic land certificate implementation to include enhanced data protection systems and digital bureaucracy accountability measures and flexible legal oversight that protects community rights through technological advancements.